PlanTEA: Supporting planing and anticipation for children with ASD attending medical appointments - Hernández, Patricia; Molina, Ana; Lacave, Carmen; Rusu, Cristian; Toledano González, Abel (MDPI, 2022)
In people with Autism Spectrum Disorder (ASD), skills related to anticipation and mental flexibility are often impaired, so their thinking tends to be very rigid and their behavior is based on establishing routines. For this reason, children with ASD may show disruptive behaviors when faced with disturbing but necessary activities, such as going to a doctor’s appointment. Therefore, it is very convenient and necessary for their families to prepare in advance for the visit and to explain the details of the procedure to be performed at the consultation. The use of anticipation boards in these situations allows to prepare such situations and to reduce stress for both the ASD child and their families or caregivers. In this context, the use of technology can provide great benefits for anticipating a new event, or whatever risks the control of their routines, as well as enhancing developmental skills such as communication, autonomy, social interaction, etc. This article describes a software tool, for mobile devices such as tablets, that allows the planning of the attendance of children with ASD to the necessary medical appointments throughout their childhood and adolescence, as well as communication with specialists. This app, named PlanTEA, has undergone a preliminary evaluation that has yielded very positive results. Most participants found the app useful in helping to anticipate (94.1%) and improve communication (94.2%) for people with ASD in medical contexts, considered it easy to use, with no technical support needed to use it (almost 100%), and would recommend its use (94.2%). This first evaluation has also allowed us to define the next steps to be taken to improve and enhance this tool and thus reach a wider population within the autistic disorder. As a result of the evaluation carried out and the comments received, it is proposed to extend its use to adult users and those with high-functioning autism.
Keywords: Autismo .- Innovaciones tecnológicas; Autism Spectrum Disorder; Children; Medical Appointments; Mobile Application; Usability; User Experience